2020
DOI: 10.1371/journal.pone.0229592
|View full text |Cite
|
Sign up to set email alerts
|

Level and determinants of postpartum adherence to antiretroviral therapy in the Eastern Cape, South Africa

Abstract: BackgroundAdherence to antiretroviral therapy (ART), especially during the postpartum period, remains a major challenge in the efforts towards eliminating mother-to-child transmission of HIV. This study examined the levels and determinants of postpartum adherence to ART among mothers with HIV in the Eastern Cape, South Africa. MethodsIn this cross-sectional analytical study, we interviewed 495 postpartum women with HIV between January and May 2018. We measured postpartum adherence using six questions probing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
12
2
Order By: Relevance
“… 73 Independent of breastfeeding, alcohol use post-delivery may exacerbate other postpartum stressors and negatively impact ART adherence and retention in HIV care. 74 There is also a strong association between alcohol use postpartum and maternal depression. 75 77 As another limitation, the parent study did not use the full version of the modified Brief COPE scale, which precluded analysis that might have revealed important relationships between coping styles assessed by specific subscales (eg, avoidance, alcohol use to cope) and the 4 alcohol use groups.…”
Section: Discussionmentioning
confidence: 99%
“… 73 Independent of breastfeeding, alcohol use post-delivery may exacerbate other postpartum stressors and negatively impact ART adherence and retention in HIV care. 74 There is also a strong association between alcohol use postpartum and maternal depression. 75 77 As another limitation, the parent study did not use the full version of the modified Brief COPE scale, which precluded analysis that might have revealed important relationships between coping styles assessed by specific subscales (eg, avoidance, alcohol use to cope) and the 4 alcohol use groups.…”
Section: Discussionmentioning
confidence: 99%
“…Responses from 319 parturient women, who confirmed that they had initiated complementary feeding before six months to their infants, were analysed thematically in this sub-study. All mothers were on antiretroviral therapy, however, close to one in three women reported adherence challenges [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Disengagement from care among postpartum WRLHIV is common in SA and other high HIV burden countries and may lead to women becoming viraemic as a result of non-adherence to ART. [31][32][33] In SA, this has important programmatic implications given the extended breastfeeding period of up to 24 months among WRLHIV on ART. [34] In order to achieve eMTCT, the programme requires better systems for tracking WRLHIV throughout pregnancy and the postpartum period to enable retention in care and efficient VL monitoring to guide clinical management in this population.…”
Section: Researchmentioning
confidence: 99%